Room temperature atomic frequency comb storage for light - Main, D; Hird, TM; Gao, S; Walmsley, IA; Ledingham, PM (Optical Society of America, 2021)
We demonstrate coherent storage and retrieval of pulsed light using the atomic frequency comb protocol in a room temperature alkali vapor. We utilize velocity-selective optical pumping to prepare multiple velocity classes in the 𝐹=4 hyperfine ground state of cesium. The frequency spacing of the classes is chosen to coincide with the 𝐹′=4−𝐹′=5 hyperfine splitting of the 62P3/2 excited state, resulting in a broadband periodic absorbing structure consisting of two usually Doppler-broadened optical transitions. Weak coherent states of duration 2ns are mapped into this atomic frequency comb with pre-programmed recall times of 8ns and 12ns, with multi-temporal mode storage and recall demonstrated. Utilizing two transitions in the comb leads to an additional interference effect upon rephasing that enhances the recall efficiency.